Anti-inflammatory properties of phenolic lactones isolated from Caesalpinia paraguariensis stem bark - Sgariglia, Melina Araceli (2013)
Ethnopharmacological relevance Caesalpinia paraguariensis (D. Parodi) Burkart stem bark infusion (CPBI) is traditionally used in Argentina because their “vulnerary” properties. Aim of the study CPBI was studied throughout bio-guided purification procedures conducted by in vitro biological assays in order to isolate the main bioactive compounds. Material and methods Anti-inflammatory activity was assessed by enzyme inhibition assays of Hyaluronidase (Hyal) and inducible Nitric Oxide Synthase (iNOS). The antioxidant properties were evaluated by DPPH free radical scavenging assay, lipid peroxidation inhibition assay on erythrocyte membranes, and a cell-based assay that included the fluorescent probe (DCFH-DA) for indicating reactive oxygen species (ROS) generation. Bioactive compounds were purified by chromatographic methods and their structures elucidated using spectroscopic methods (ESI-MS and 1D/2D-1H/13C-NMR). Results Four main bioactive compounds were isolated from CPBI: ellagic acid (1), 3-O-methylellagic acid (2), 3,3'-di-O-methylellagic acid (3) and 3,3'-di-O-methylellagic-4-β-D-xylopyranoside (4). These were bioactive at concentrations in which are present in CPBI, being compounds 2 and 3 the best enzyme inhibitors of Hyal and iNOS, reaching the 90% inhibitory concentration (IC90) values ranging from 2.8 to 16.4 μM, that are better than that of the positive controls, aspirin (IC90: no reached) and aminoguanidine (IC90: 20.2 μM) respectively. Compounds 2 and 3 were also better scavengers for lipoperoxides than butylated hydroxytoluene (BHT), reaching the 90% effective concentration (EC90) at 1.2–4.5 μg/ml, and for DPPH radical (2.5–7.3 μg/ml); moreover compounds were able to exert its scavenging action on intracellular ROS. Structural features relevant to the biological activities are discussed. Conclusions This work provides scientific validity to the popular usage of CPBI.